2014
DOI: 10.4161/15384101.2014.947759
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of STAT4 expression in cutaneous T-cell lymphoma (CTCL) patients and patient-derived cell lines

Abstract: Deregulation of STAT signaling has been implicated in the pathogenesis for a variety of cancers, including CTCL. Recent reports indicate that loss of STAT4 expression is an important prognostic marker for CTCL progression and is associated with the acquisition of T helper 2 cell phenotype by malignant cells. However, little is known about the molecular mechanism behind the downregulation of STAT4 in this cancer. In the current work we test the expression of STAT4 and STAT6 via RT-PCR and/or Western Blot in CTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 63 publications
1
60
1
4
Order By: Relevance
“…HDAC inhibitors may restore this balance because treatment with HDAC inhibitors have been shown to upregulate STAT-4 and decrease STAT-6 in vitro. 16 …”
Section: Mechanism Of Action Of Histone Deacetylase Inhibitorsmentioning
confidence: 97%
See 2 more Smart Citations
“…HDAC inhibitors may restore this balance because treatment with HDAC inhibitors have been shown to upregulate STAT-4 and decrease STAT-6 in vitro. 16 …”
Section: Mechanism Of Action Of Histone Deacetylase Inhibitorsmentioning
confidence: 97%
“…15 The STAT family of transcription factors (STAT-3, -4, -5, and -6) are thought to have a key role in driving T-cell proliferation in CTCL. 16 STAT-4, associated with a T helper cell (Th) 1 phenotype, is downregulated in CTCL cell lines, whereas STAT-6, which is associated with Th2 phenotype, is upregulated. Change in STAT expression could contribute to the TH1 to TH2 phenotype switch seen in disease progression.…”
Section: Mechanism Of Action Of Histone Deacetylase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-155 has been dubbed as the "bridge between inflammation and cancer" because a transient increase in this miRNA leads to activation of several types of immune cells, while constitutive up-regulation of this gene results in the development of malignancies as a result of increased genomic instability [48] [49]. In a recent study, Litvinov et al demonstrated that STAT4 is one of the targets of miR-155 [46]. In summary, STAT signaling appears to play a central role in the pathogenesis of this cancer where early in the disease STAT5 up-regulation drives the expression of miR-155 oncogene, [4].…”
Section: The Inverse Correlation Between Stat4 and Mir155mentioning
confidence: 99%
“…In particular, Nebozhyn M. et al demonstrated that STAT4 protein levels in purified CD4 + cells from patients with SS were reduced or absent [45]. STAT4 activity, which is required for T helper (Th) 1 differentiation, is induced by IL-12 cytokine, which is profoundly deficient in CTCL patients [46]. STAT4 expression is subsequently lost at later clinical stages, when the disease predominantly acquires the Th2 phenotype [47].…”
Section: The Inverse Correlation Between Stat4 and Mir155mentioning
confidence: 99%